Routledge handbook of political corruption - Heywood, Paul. (Routledge; London and New York:., 2018)
"his Handbook provides a showcase to the most innovative and exciting research being conducted in the field of political corruption, as well as providing a new point of reference for all who are interested in the topic"--
Includes bibliographical references and index.
Keywords: Political corruption; POLITICAL SCIENCE / General; POLITICAL SCIENCE / International Relations / General